The Impact of Donor–Acceptor Phase Separation on the Charge Carrier Dynamics in pBTTT:PCBM Photovoltaic Blends. Issue 11 (7th April 2015) - Gehrig, Dominik W.; Howard, Ian A.; Sweetnam, Sean; Burke, Timothy M.; McGehee, Michael D.; Laquai, Frédéric; Char, K.; Zentel, R.
<x xml:space="preserve">Abstract</x> The effect of donor–acceptor phase separation, controlled by the donor–acceptor mixing ratio, on the charge generation and recombination dynamics in pBTTT‐C14:PC70BM bulk heterojunction photovoltaic blends is presented. Transient absorption (TA) spectroscopy spanning the dynamic range from pico‐ to microseconds in the visible and near‐infrared spectral regions reveals that in a 1:1 blend exciton dissociation is ultrafast; however, charges cannot entirely escape their mutual Coulomb attraction and thus predominantly recombine geminately on a sub‐ns timescale. In contrast, a polymer:fullerene mixing ratio of 1:4 facilitates the formation of spatially separated, that is free, charges and reduces substantially the fraction of geminate charge recombination, in turn leading to much more efficient photovoltaic devices. This illustrates that spatially extended donor or acceptor domains are required for the separation of charges on an ultrafast timescale (<100 fs), indicating that they are not only important for efficient charge transport and extraction, but also critically influence the initial stages of free charge carrier formation.